The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3122/jabfm.17.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Consumer Advertising: Public Perceptions of Its Effects on Health Behaviors, Health Care, and the Doctor-Patient Relationship

Abstract: Purpose: To determine public perceptions of the effect of direct-to-consumer advertising (DTCA) of prescription medications on health behaviors, health care utilization, the doctor-patient relationship, and the association between socioeconomic status and these effects.Methods: Cross-sectional survey of randomly selected, nationally representative sample of the US public using computer-assisted telephone interviewing. Main outcome measures: numbers and proportions of respondents in the past 12 months who, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
109
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 14 publications
0
109
3
1
Order By: Relevance
“…To date, no one has analyzed systematically what television ads claim about health conditions, how they attempt to appeal to consumers, or how they portray the role of lifestyle behaviors and medication in achieving good health. These questions are critically important given evidence that DTCA prompts consumers to request prescriptions for advertised products from their physicians, 14,15 and that many of those requests are fulfi lled despite being judged clinically inappropriate. 16 The goal of our study was to analyze the content of television DTCA messages to lay the foundation for future studies that examine the consequences of DTCA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no one has analyzed systematically what television ads claim about health conditions, how they attempt to appeal to consumers, or how they portray the role of lifestyle behaviors and medication in achieving good health. These questions are critically important given evidence that DTCA prompts consumers to request prescriptions for advertised products from their physicians, 14,15 and that many of those requests are fulfi lled despite being judged clinically inappropriate. 16 The goal of our study was to analyze the content of television DTCA messages to lay the foundation for future studies that examine the consequences of DTCA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers have consistently expressed a desire for information on indications and drug side effects (Foley and Gross 2000;Tucker and Smith 1987;Woloshin et al 2004;Young et al 2005). In opinion and attitude research, consumers have generally been found to have 'neutral' or 'positive' attitudes to consumer marketing of medicines as a source of information (Alliance for Access to Medical Information (AAMI) 2002; Bell et al 1999a;Beltramini 2006;Gonul et al 2000;Herzenstein et al 2004;Hoek et al 2004;Huh et al 2004a;Huh et al 2004b;Miller and Waller 2004;Murray et al 2004;National Consumers League 2003;Perri and Nelson Jr. 1987;Robinson et al 2004;Vatjanapukka 2004). However exposure to consumer marketing of medicines does not appear to improve the accuracy of consumers' knowledge about drugs (Brodie 2001;Hoek 2007;Kaphingst et al 2005), and consumers generally express skepticism about the quality and credibility of information provided by such marketing and conflicting, diverse or inconsistent attitudes on the benefits and risks posed by it (Alperstein and Peyrot 1993;Foley and Gross 2000;Herzenstein et al 2004;Marinac et al 2004;Miller and Waller 2004;Robinson et al 2004;Young et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…10 DTC ads have the potential to increase the appropriateness of prescribing among those who have a condition for which medication is underprescribed, 11,12 but the (potentially adverse) effect on the many who see the message but who do not have the condition is inherently harder to measure. 7,13 Together, these sources show an emerging public health tragedy that is happening so surreptitiously that we are blind to the magnitude of the encroaching effect on the quality of health care and the health of Americans.…”
mentioning
confidence: 99%
“…The process 4,13 and consequences 10,[13][14][15] of DTC ads are complex, infl uenced by a multifaceted interaction between the prevalence and severity of the condition to be treated, the effectiveness of the treatment, the severity and frequency of side-effects, and the degree to which the condition is over-or undertreated in the population. 2,16 The public health impact of the ads on diverse individuals also depends on intricately interrelated characteristics of the DTC advertisement.…”
mentioning
confidence: 99%
See 1 more Smart Citation